Effect of Phosphorus Concentration on Sea Grape Growth Rate (Caulerpa racemosa) - Amrina Rossada, Rizky; Cokrowati, Nunik; Prasedya, Eka Sunarwidhi (Department of Aquaculture, 2025)
Sea grapes are one type of seaweed in Indonesia. One of them is Caulerpa racemosa. This study was conducted to determine the effect of phosphorus concentration on the growth rate of C. racemosa with different doses of fertilizer. This study was designed using a completely randomized design (CRD) consisting of four treatments and three replicates. The dose used is 0 ppm (control), 1.5 ppm, 3 ppm, and 4.5 ppm. C. racemosa were reared for 15 days in 35 cm plastic containers with a volume of water used during the rearing period of 10 liters, equipped with aerators and small aeration bubbles set with a stocking density of 25 grams. The results showed that the daily growth rate (DGR) of sea grapes ranged from 5.6-17.55%, final weight ranged from 10-31.3 g, antioxidant activity ranged from 30.49-38.66%, and chlorophyll content ranged from 26.21-31.35 mg/L. The DGR of C. racemosa was not substantially affected (p>0.05) by the fertilizer formulation dose concentrations. Further research needs to be done by adding phosphorus fertilizer doses for standard daily growth rate results.